Evaluating relative contribution of osmotolerance and tissue tolerance mechanisms toward salinity stress tolerance in three Brassica species. Issue 2 (5th July 2016) - Chakraborty, Koushik; Bose, Jayakumar; Shabala, Lana; Eyles, Alieta; Shabala, Sergey
Abstract : Three different species of Brassica, with differential salt sensitivity were used to understand physiological mechanisms of salt tolerance operating in these species and to evaluate the relative contribution of different strategies to cope with salt load. Brassica napus was the most tolerant species in terms of the overall performance, with Brassica juncea and Brassica oleracea being much more sensitive to salt stress with no obvious difference between them. While prominent reduction in net CO2 assimilation was observed in both sensitive species, physiological mechanisms beyond this reduction differed strongly. Brassica juncea plants possessed high osmotolerance and were able to maintain high transpiration rate but showed a significant reduction in leaf chlorophyll content and efficiency of leaf photochemistry. On the contrary, B. oleracea plants possessed the highest (among the three species) tissue tolerance but showed a very significant stomatal limitation of photosynthesis. Electrophysiological experiments revealed that the high tissue tolerance in B. oleracea was related to the ability of leaf mesophyll cells to maintain highly negative membrane potential in the presence of high apoplastic Na + . In addition to high osmotolerance, the most tolerant B. napus showed also lesser accumulation of toxic Na + and Cl − in the leaf, possessed moderate tissue tolerance and had a superior K + retention ability. Taken together, the results from this study indicate that the three Brassica species employ very different mechanisms to cope with salinity and, despite its overall sensitivity to salinity, B. oleracea could be recommended as a valuable 'donor' of tissue tolerance genes to confer this trait for marker‐assisted breeding programs.